Association of TLR3 gene 1377C/T (rs3775290) and TLR7 gene C/G (rs3853839) polymorphism with hand, foot, and mouth disease caused by human enterovirus 71 infection susceptibility and severity in the Chinese Han population: A meta-analysis of case-control studies. Issue 27 (8th July 2022) - Tian, Haokun; Xu, Weikai; Wen, Lequan; Tang, Lirui; Zhang, Xinyuan; Song, Tiangang; Yang, Changsen
Abstract : Background: Several case-control studies have been conducted on the relationship between rs3775290 C/T and rs3853839 C/G single nucleotide polymorphisms of the Toll-like receptor (TLR) gene and hand, foot, and mouth disease (HFMD) susceptibility and severity. This meta-analysis aimed to offer a systemic review of HFMD susceptibility and severity among the Chinese Han population associated with the C/T (rs3775290) polymorphism of the TLR3 gene or C/G (rs3853839) polymorphism of the TLR7 gene. Methods: A computer search was conducted using PubMed, Web of Science, Embase, CNKI, CBM, VIP, and WanFang databases. The time ranges were from database establishment to 30/7/2021. Articles selected according to the inclusion and exclusion criteria underwent data extraction and methodological quality evaluation. RevMan 5.4 and Stata 16.0 were adopted for meta-analysis, and the incorporated odds ratio (OR) values and 95% confidence intervals (CIs) were calculated. Sensitivity and publication bias assessments were performed. Results: 8 articles with 9 studies were selected. Among them, there were 858 cases and 577 controls in TLR3 rs3775290 studies as well as 2151 cases and 1554 controls in TLR7 rs3853839 studies. Regarding rs3775290 of TLR3, susceptibilities of the severe type of T-possessing individuals were larger than those of C-possessing individuals [OR = 1.34, 95%CI (1.10, 1.64), P = .004]. The susceptibility of individuals with the severe TT genotype was 1.61 times that of individuals with the CC genotype [95%CI (1.07, 2.43), P =0.02], while susceptibility to HFMD was not influenced by the genotype. In terms of the rs3853839 of the TLR7 gene, C allele carriers have a higher risk of developing HFMD than G allele carriers. The susceptibility to HFMD in CC+CG individuals was 1.24 times than that in GG individuals [95%CI (1.07, 1.43), P = .004]. However, no relationship was found between this polymorphism and severity of the severe type. No significant publication bias was observed in this study. Conclusions: rs3775290 (C/T) of TLR3 is associated with susceptibility to the severe type, whereas rs3853839 (C/G) of TLR7 is associated with susceptibility to HFMD. However, owing to the limited quantity and quality of the research, the aforementioned conclusions are yet to be justified by more high-quality research.